Penerapan Model Deep Learning Terhadap Perkembangan Bahasa Pada Anak Usia Dini - Alika Adina Ajaib Tabe; Yunita Tampani; Semsry Lakes; Juan Flegon Fernando Moni; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Language development is a crucial aspect of early childhood growth, serving as the foundation for children to communicate, interact, and understand their surroundings. However, challenges hindering the optimization of children's language skills persist in early childhood education settings. This study aims to examine the implementation of the deep learning model regarding the language development of 21 children aged 5–6 years at PAUD Hosana Sungkaen. Language proficiency forms the basis for children to communicate, interact, and comprehend the world around them. The study employs a descriptive approach with quantitative methods, utilizing observation and educator interviews for data collection. The findings reveal that the deep learning model influences language development in children aged 5–6 years, with an R-squared value of 0.892; this indicates that the deep learning model accounts for 89.2% of the impact on language development, while the remaining 10.8% is attributed to factors not examined in this study. It is recommended that teachers implement the deep learning model to foster language development through engaging activities—such as storytelling, question-and-answer sessions, and play—thereby enabling children to communicate effectively and confidently.